Study on layer fabrication for 3D structure of photoreactive polymer using DLP projector - K., Khairu; M ., Ibrahim; Hassan, S.; Hehsan, H.; Kasmin, Ashari; E., Fazial (Trans Tech Publications, 2014)
This paper presents a research on 3D part fabrication from composition of photo initiator (Phenylbis(2,4,6-trimethylbenzoyl)), photo absorber (Sudan I) and 1, 6- Hexanediol polymer effect based on curing parameters. A DLP projector was used as energy light source which initiated the photo reactive polymer at three different light source distances with three different exposed time to evaluate photoreactive polymer solidification phenomena. The experiment results obtained shows that Sudan I composition, light intensity value and exposure time of the varied photo absorber give significant effect to layer thicknes, surface roughness and hardness value. These works also prove that photo absorber composition solution gave a different mechanical properties effect for 3D microstructure fabrication.